Comparison of 2 interferometers for predicting visual acuity in patients with cataract. Issue 5 (May 1983) - Halliday, B L; Ross, J E
Abstract : Two clinical interferometers generated gratings directly on to the retina in young experienced observers and also in patients about to undergo cataract surgery. Eyes in the patients with no media opacities were used as controls. We agreed with the manufacturers' claims that gratings are seen on the retina independent of refractive state and that gratings can still be seen through most cataracts. However, we did not find that preoperative retinal visual acuity was of any value in predicting postoperative Snellen visual acuity. Reasons for this are discussed.